What it means to be an ally in Indigenous healthcare - Bruno, Margaux; Oster, Richard T; Mayan, Maria J (Canadian Medical Education Journal, 2024)
Background: Strengths-based and culturally sensitive approaches to Indigenous healthcare are much needed within the Canadian healthcare system. This is where allyship comes in. Allyship is loosely defined as the actions of an individual who strives to advance the interests of marginalized groups in which they are not a member. This study investigated the concept of allyship with healthcare providers who were community-identified allies providing care for Indigenous patients. Methods: Qualitative description methodology was utilized, and data was generated through semi-structured interviews with allies in and around the Edmonton area, in Canada. The interviews were conducted online, transcribed verbatim and then coded using thematic analysis. Results: Interviews were conducted with 13 allies (eight physicians, four allied health professionals and one nurse). The results were captured into three main themes. The meaning of allyship demonstrated how allyship must be determined by the community, and encapsulates authentic action and advocacy, as well as working to create positive healthcare experiences. The experience of being an ally included commitment to the allyship journey, embracing emotions, and facing and disrupting systemic barriers. Finally, cultivating allyship in healthcare necessitated building and maintaining meaningful relationships with Indigenous people, and ongoing training and education. Conclusion: The study results enabled a better understanding of how allies interact with their Indigenous patients within the confines of the healthcare system and could inform learning opportunities for those who seek to practice in a culturally humble way. In particular, transcending passive education and training modalities to include opportunities for real life interactions and the development of reciprocal relationships with Indigenous patients.